Clinical and genetic analysis in Chinese families with synpolydactyly, and cellular localization of HOXD13 with different length of polyalanine tract - Chen, Xiumin; Zhao, Feiyue; Xu, Yiming; Cao, Yixuan; Li, Shan; Zhang, Xue; Zhao, Xiuli (Frontiers in Genetics, 2023)
Synpolydactyly (SPD) is caused by mutations in the transcription factor gene HOXD13. Such mutations include polyalanine expansion (PAE), but further study is required of the phenotypic spectrum characteristics of HOXD13 PAE. We investigated four unrelated Chinese families with significant limb malformations. Three duplication mutations were found in the HOXD13 PAE region: c.172_192dup (p.Ala58_Ala64dup) in family 1, c.169_192dup (p.Ala57_Ala64dup) in family 2, and c.183_210dup (p.Ala62_Ala70dup) in families 3 and 4. Interestingly, we identified a new manifestation of preaxial polydactyly in both hands in a pediatric patient with an expansion of seven alanines, a phenotype not previously noted in SPD patients. PAE affects the nucleation of HOXD13 protein and the effect intensifies as the PAE length increases. These findings expand the phenotypic spectrum and advance our understanding of human limb development.